2022
DOI: 10.3390/rs14143249
|View full text |Cite
|
Sign up to set email alerts
|

Machine Learning Techniques for Phenology Assessment of Sugarcane Using Conjunctive SAR and Optical Data

Abstract: Crop phenology monitoring is a necessary action for precision agriculture. Sentinel-1 and Sentinel-2 satellites provide us with the opportunity to monitor crop phenology at a high spatial resolution with high accuracy. The main objective of this study was to examine the potential of the Sentinel-1 and Sentinel-2 data and their combination for monitoring sugarcane phenological stages and evaluate the temporal behaviour of Sentinel-1 parameters and Sentinel-2 indices. Seven machine learning models, namely logist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 76 publications
0
0
0
Order By: Relevance
“…Even if we observed an increase in prediction accuracy over using one of both sensors alone, we could not clearly confirm the findings by Mercier et al (2020), who found an improvement by combining S1 and S2 data for their phenology classification algorithm. This synergy was also suggested by Harfenmeister et al (2021), Veloso et al (2017), andYeasin et al (2022) who found vastly different but also complementary performances of SAR and optical time series for analyzing the phenology of winter wheat, barley and sugarcane. The improvement for some stages could be attributed to uncertainties and ambiguities in the predictions with SAR or optical data alone, respectively, that could be resolved by combining both.…”
Section: Feature Combinationsmentioning
confidence: 53%
See 2 more Smart Citations
“…Even if we observed an increase in prediction accuracy over using one of both sensors alone, we could not clearly confirm the findings by Mercier et al (2020), who found an improvement by combining S1 and S2 data for their phenology classification algorithm. This synergy was also suggested by Harfenmeister et al (2021), Veloso et al (2017), andYeasin et al (2022) who found vastly different but also complementary performances of SAR and optical time series for analyzing the phenology of winter wheat, barley and sugarcane. The improvement for some stages could be attributed to uncertainties and ambiguities in the predictions with SAR or optical data alone, respectively, that could be resolved by combining both.…”
Section: Feature Combinationsmentioning
confidence: 53%
“…(2020) and Yeasin et al (2022). Both reported improvements over single-sensor models, supporting the assumption of data complementarity for phenological analyses.…”
Section: Introductionmentioning
confidence: 65%
See 1 more Smart Citation
“…Application of the logistic regression approach to a wide range of applied tasks is part of the mainstream of geophysical research, especially in marine geophysics [45][46][47][48][49][50][51][52]; for example, this approach is used for the study of changes in soil properties [45], ocean processes [46], etc. However, such an approach is rarely used for soil classification of the sea bottom.…”
Section: Discussionmentioning
confidence: 99%